Paper 11: Utility of Objective Testing for Initiation of a Throwing Program Following Shoulder and Elbow Surgery in Competitive Baseball Players. Issue 7 (30th July 2022) - Sgroi, Terrance; Estrada, Jennifer; Mcelheny, Kathryn; Dines, Joshua; Altchek, David; Carr, James
Objectives: The timing for initiation of a throwing program following shoulder or elbow surgery in an overhead throwing athlete is dependent on a variety of factors, including surgical procedure performed, time from surgery, level of competition, and successful progression through a physical therapy program. Determining when it is safe for an athlete to begin a post-surgical throwing program is vitally important to ensure safe return to play, and objective data is often preferred to help accurately make such decisions. However, there is a paucity of objective data available to help guide the decision for the timing of initiation of a throwing program following shoulder and elbow surgery in overhead throwing athletes. Additionally, it is unknown what percentage of athletes typically achieve appropriate objective criteria at the presumed timepoint for initiation of a throwing program. Therefore, the objectives of the current study were the following: 1) to create a reproducible, objective return to throwing protocol, 2) to determine what percentage of post-surgical competitive baseball players successfully satisfied the objective return to throwing criteria at the presumed time of throwing program initiation, and 3) to determine what risk factors were most common in athletes who failed to meet objective criteria for return to throwing. Methods: Patients who were a competitive overhead throwing athlete and who underwent a shoulder or elbow surgery by one of the two senior authors were given the opportunity to perform an objective return to throwing evaluation at the presumed time of clearance by the treating physician. Figure 1 outlines the objective return to throwing criteria with the desired goal for each criterion. Each evaluation was performed by a single physical therapist with extensive experience in rehabilitation of overhead athletes. Patients who successfully accomplished all criteria at the time of evaluation were given a passing grade. Patients who failed the initial objective evaluation were re-tested two weeks later. Surgical procedure, level of play, and reason for failing were recorded for all players. Kinematic variables were compared between patients who passed versus those who failed using a two-tailed student's t-test. Relative odds and risks ratios were assessed for level of play and type of surgery with 95% confidence intervals. Significance was set at p<0.05 for all tests. Results: A total of 48 players were evaluated, and level of play was divided into high school (20 patients), college (19 patients), and professional (8 patients). A total of 36 players (75%) obtained a passing grade at the initial evaluation while 12 players received a failing grade (25%). The distribution of passing grades based on surgery type was the following: arthroscopic shoulder surgery: 4/7 patients, UCL reconstruction: 23/31 patients, UCL repair: 3/3 patients, and other elbow surgery (i.e. ulnar nerve decompression transposition, isolated elbow arthroscopy): 5/6 patients. Level of play, type of surgery, and reason for failing is summarized for all players who received a failing grade (Table 1). All players who failed were retested at two weeks and received a passing grade after focused physical therapy to address any insufficiencies. Players who received a failing grade demonstrated significantly more elbow extension, less dominant arm maximum shoulder internal rotation strength, and less dominant arm maximum shoulder external rotation strength (Table 2). Players with a level of play beyond high school and college each showed an elevated odds ratio and relative risk for receiving a failing grade, yet this did not reach statistical significance. Undergoing ulnar collateral ligament reconstruction demonstrated a trend towards having a smaller odds ratio for a failing grade, but this also did not reach statistical significance (Table 3). Conclusions: The most important finding of the current study is that 25% of competitive baseball players did not pass an objective return to throw evaluation at the time of presumed clearance based on time from surgical procedure and objective in-office evaluation by the treating surgeon. All patients who failed were able to achieve a passing grade two weeks later after directed physical therapy to address all insufficiencies. No specific factor reached statistical significance for increasing the odds ratio or relative risk for receiving a failing grade, though undergoing UCL reconstruction demonstrated an insignificant trend for having a lower risk of failing. Our findings demonstrate that not all competitive baseball players will be objectively ready to throw at the presumed time point following shoulder and elbow surgery, and insufficient shoulder strength and/or endurance was the most common reason for failure. Creating objective criteria to help determine when to start a post-surgical throwing program is a critical step to ensure safe rehabilitation after shoulder and elbow surgery in competitive baseball players. The current study provides a foundation for establishing such objective criteria, and it highlights areas of improvement in rehabilitation protocols. Further research is needed to validate the objective testing protocol and its applicability in a larger population. Figure 1. Checklist for objective return to throwing criteria. To obtain a passing score, the patient must achieve a "Yes" by attaining the minimum goal for each criterion. Table 1. Level of play, surgical procedure, and reason for failing for all patients who received an initial failing grade from objective return to throw testing Table 2. Descriptive statistics for time since surgery and throwing arm joint kinematics and kinetics for all players and within passing/failing groups Table 3. Relative odds and risk ratios for passing the return-to-throw test with respect to noted criteria